2014
DOI: 10.21101/cejph.a3797
|View full text |Cite
|
Sign up to set email alerts
|

Do Eating Habits of the Population Living in Roma Settlements Differ from Those of the Majority Population in Slovakia?

Abstract: Living in Roma settlements is associated with worse health in comparison with the majority population; this might be partially explained by socioeconomic disadvantages as well as cultural differences, including lifestyle. Eating habits represent an important part of lifestyle closely related to primary causes of morbidity and mortality, such as cardiovascular diseases, metabolic diseases or cancers. The eating habits of the population living in Roma settlements in comparison with those of the majority populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Despite notable exceptions indicating equal or healthier social support (Bobakova et al 2015; Kolarcik et al 2012), alcohol and illicit drug use (Babinska et al 2014; Kolarcik et al 2010) and sexual behaviours (Halanova et al 2014), rigorous studies show that overall Slovak segregated Roma engage in riskier health-related practices than the rest of the population. For example, higher levels of smoking (Belak 2013; Jarcuska et al 2013), an unhealthier diet (Hijova et al 2014; Krajcovicova-Kudlackova et al 2004), unhealthier physical activity (Babinska et al 2014; Kolarcik et al 2010), the maintenance of riskier material conditions (Filadelfiova and Gerbery 2012; Majdan et al 2012) and less effective healthcare use (Belak 2013; Jarcuska et al 2013) are found among these Roma.…”
Section: Introductionmentioning
confidence: 99%
“…Despite notable exceptions indicating equal or healthier social support (Bobakova et al 2015; Kolarcik et al 2012), alcohol and illicit drug use (Babinska et al 2014; Kolarcik et al 2010) and sexual behaviours (Halanova et al 2014), rigorous studies show that overall Slovak segregated Roma engage in riskier health-related practices than the rest of the population. For example, higher levels of smoking (Belak 2013; Jarcuska et al 2013), an unhealthier diet (Hijova et al 2014; Krajcovicova-Kudlackova et al 2004), unhealthier physical activity (Babinska et al 2014; Kolarcik et al 2010), the maintenance of riskier material conditions (Filadelfiova and Gerbery 2012; Majdan et al 2012) and less effective healthcare use (Belak 2013; Jarcuska et al 2013) are found among these Roma.…”
Section: Introductionmentioning
confidence: 99%
“…Higher smoking rates, less physical activity, riskier dietary habits and greater perceived healthcare access barriers have all been found in rigorous comparative studies (e.g. Babinska et al 2013;Hijova et al 2014;Jarcuska et al 2013). Other research indicates poor community and personal hygienic standards, a missing or dysfunctional basic infrastructure, increased environmental hazards, overcrowding and even food shortages (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Rigorous scientific studies have found the segregated Roma in Slovakia to live in unhealthier material circumstances (Frisman et al 2015;Majdan et al 2012;Škobla et al 2016) (for an illustration, see Figure 1.6), to smoke and use illicit drugs more frequently (Babinska et al 2013;e.g. de Courten et al 2003;Hubková et al 2018;Vazan et al 2011), to eat an unhealthier diet and be more obese (Hijova et al 2014;Krajcovicova-Kudlackova et al 2004;Petrásová et al 2014) and to engage in less healthy physical activities and incur more injuries Babinska et al 2013;Kolarcik et al 2010). Slovak segregated Roma were also found to face greater healthcare-access barriers (Bobakova et al 2015;Kolarcik et al 2015) and to rate their health as worse (Geckova et al 2014;Kolarcik et al 2009).…”
Section: Pathways In Slovakiamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we examined a Roma population for some anthropometrical and biochemical parameters. In previous studies, we have demonstrated that Roma compared to non-Roma had higher rates of some cardiovascular disease risk factors (smoking, obesity, low HDL cholesterol) [ 17 ], metabolic syndrome [ 2 , 5 ], a lack of physical activity [ 18 ], as well as unhealthy eating habits [ 19 ]. The primary aim of the present study was to determine a comprehensive biochemical profile and ethnicity-specific associations of serum uric acid with cardiometabolic and hepatorenal health factors in Eastern Slovakian Roma and non-Roma populations.…”
Section: Introductionmentioning
confidence: 99%